2020
DOI: 10.3390/diagnostics10110945
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adiponectin and Tumor Necrosis Factor-Alpha in the Pathogenesis and Evolution of Type 1 Diabetes Mellitus in Children and Adolescents

Abstract: Type 1 diabetes mellitus (T1DM) is a complex condition caused by the destruction of pancreatic beta cells by autoimmune mechanisms. As a result, insulin deficiency and subsequent hyperglycemia occur. The aim of the present study is to investigate the role of adiponectin and tumor necrosis factor alpha (TNF-α) in the development of T1DM. The study is designed as an observational case-control study, involving 52 diabetic patients and 66 controls. Z scores for Body Mass Index (BMI), weight, height, and adiponecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Moreover, HOTAIR expression was found to be markedly increased following tumor necrosis factor-alpha gene (TNFA) stimulation [ 56 ]. TNFA contributes to the pathogenesis of a variety of inflammatory diseases as well as type 1 diabetes mellitus (T1DM) in children and adolescents [ 57 , 58 ]. Irregularity in GSK-3 β gives rise to diabetic encephalopathy [ 59 ], diabetic cardiomyopathy [ 60 ], maternal type 1 diabetes [ 61 ], T1DM [ 62 ], and other types of diabetes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HOTAIR expression was found to be markedly increased following tumor necrosis factor-alpha gene (TNFA) stimulation [ 56 ]. TNFA contributes to the pathogenesis of a variety of inflammatory diseases as well as type 1 diabetes mellitus (T1DM) in children and adolescents [ 57 , 58 ]. Irregularity in GSK-3 β gives rise to diabetic encephalopathy [ 59 ], diabetic cardiomyopathy [ 60 ], maternal type 1 diabetes [ 61 ], T1DM [ 62 ], and other types of diabetes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, adiponectin was positively correlated with C-peptide. The predicted adiponectin concentrations at 1 month, 6 months, and 12 months of T1D follow-up, respectively, were associated with distinct progression patterns of T1D after the establishment of diagnosis [ 29 ]. High adiponectin levels were found to be correlated with poor diabetes control, while dyslipidemia, lower concentrations of adiponectin, and higher levels of inflammatory and endothelial biomarkers were correlated with obesity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predicted adiponectin concentrations at 1 month, 6 months, and 12 months of T1D follow-up, respectively, were associated with distinct progression patterns of T1D after the establishment of diagnosis [ 29 ]. High adiponectin levels were found to be correlated with poor diabetes control, while dyslipidemia, lower concentrations of adiponectin, and higher levels of inflammatory and endothelial biomarkers were correlated with obesity [ 29 ]. Natural AdV36 infections were correlated with obesity and metabolic disorders in children and adults of different ethnic groups and populations in different countries [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 11.5% of Romanian children with T1DM had DKD, manifested as transitory microalbuminuria (7.7%) and incipient diabetic nephropathy (3.8%)[ 39 ]. In another research study, T1DM patients were found to have microalbuminuria in 30% of cases, representing the most common microvascular complication.…”
Section: Diagnosismentioning
confidence: 99%